A comparative study between the legal framework of ChatGPT in Malaysia and United Kingdom - Chai, Yi Cheng (2024)
The purpose of this study is to investigate the legal framework of ChatGPT in Malaysia based on UK’s legal framework involving ChatGPT. The lecturers who are teaching in universities will be our target demographic. Qualitative and exploratory research are used in this research. Using the interviewing approach, we have administered the questionnaire to 2 target individuals. Their opinions will be recorded and compared to the information found in research. The study’s findings imply that Malaysia can learn from UK regarding the legal framework involving ChatGPT, especially the AI White Paper to create a better, proper, and complete legal framework regarding ChatGPT.